2016
DOI: 10.1371/journal.pone.0168127
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Scaling for Epidemic Size in a Spatial Epidemic Model with Mobile Individuals

Abstract: In recent years, serious infectious diseases tend to transcend national borders and widely spread in a global scale. The incidence and prevalence of epidemics are highly influenced not only by pathogen-dependent disease characteristics such as the force of infection, the latent period, and the infectious period, but also by human mobility and contact patterns. However, the effect of heterogeneous mobility of individuals on epidemic outcomes is not fully understood. Here, we aim to elucidate how spatial mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…However, international traffic has not ceased and infectious individuals (who may or may not show any symptom at the time of travel) have actually travelled to different countries with the virus they contracted [ 4 , 5 ]. Recent studies have also showed that travel restriction did contribute to the control of the spreading of COVID-19 within China as well as in a global context [ 4 , 6 , 7 ]. By May 17, 2020, China had confirmed a total of 82,954 cases of COVID-19 infection, with death toll reaching 4,634.…”
Section: Introductionmentioning
confidence: 99%
“…However, international traffic has not ceased and infectious individuals (who may or may not show any symptom at the time of travel) have actually travelled to different countries with the virus they contracted [ 4 , 5 ]. Recent studies have also showed that travel restriction did contribute to the control of the spreading of COVID-19 within China as well as in a global context [ 4 , 6 , 7 ]. By May 17, 2020, China had confirmed a total of 82,954 cases of COVID-19 infection, with death toll reaching 4,634.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we adopted static networks for representing the contact patterns of individuals. If we incorporate the population flow into simulation, we can use other model frameworks considering human mobility [ 18 , 43 , 44 ], although detailed data of mobility patterns are not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…Individual-based simulations of the network model were performed to compare the epidemic outcomes under different vaccination strategies. The result indicated the effectiveness of the special vaccination strategy of Kawasaki City in a significant and early reduction of the number of rubella cases, although the epidemic size has considerable variations for simulation trials with different initial conditions [ 18 ]. Furthermore, we examined the effects of the initiation timing and the duration of the catch-up vaccination program on the epidemic outcomes under a fixed amount of total vaccinations.…”
Section: Introductionmentioning
confidence: 99%
“…Many mathematical models of the spread of infectious diseases have been proposed using differential equations [9][10][11][12] and agent-based models [13][14][15], and several studies focus on the spread of COVID-19 in various contexts [16][17][18][19][20][21][22][23][24][25][26]. These studies model only the spread of infectious diseases and do not describe economic activities mathematically.…”
Section: Introductionmentioning
confidence: 99%